The influence of heating conditions on semi-solid forming of aluminum alloys - Önsel, Mehmet. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
The use of aluminum alloys for complex parts is receiving a great deal of attentionrecently in the automotive sector worldwide. Semi-solid forming appears to be a veryattractive method for producing complex parts as it offers fewer production steps and allows using lower forming loads. In present study, the effect of heating conditions onthixoforming of A356 and AA6082 aluminum alloys was investigated. The production of afine, equiaxed, globular microstructure is a must for the success of the thixoformingprocess. The present study showed that thixotropic structure can be successfully obtained using magnetohydrodynamic (MHD) casting route for A356 alloy and strain induced meltactivated (SIMA) route for AA6082 aluminum alloy. Holding temperature, holding timeand the number of reheating steps were considered as parameters in reheating experimentsof MHD cast A356 alloy. The impact of the extent of deformation and reheating treatment parameters on the globularization of the grains in SIMA process was investigated forAA6082 alloy. Finally, A356 and AA6082 aluminum alloys were thixoformed consideringheating conditions that give most successful thixotropic structures. The microstructures and mechanical properties of the produced parts were investigated to get information about the obtained quality of the parts.
Keywords: Aluminum alloys.